(Post-) Soviet Sociologies - Zysiak, Agata (Serendipities. Journal for the Sociology and History of the Social Sciences, 2018)
Book review of: Bucholc, Marta. 2016. Sociology in Poland: To Be Continued? London: Palgrave Macmillan. 102 pp. ISBN 978-1-137-58186-0 (Hardcover) Price: € 57,19 Skovajsa, Marek and Jan Balon. 2017. Sociology in the Czech Republic: Between East and West. London: Palgrave Macmillan. 150 pp. ISBN 978-1-137-45026-5 (Hardcover) Price: € 51,99 Titarenko, Larissa and Elena Zdravomyslova. 2017. Sociology in Russia: A Brief History. Cham, Switzerland: Palgrave Macmillan. 158 pp. ISBN 978-3-319-58084-5 (Hardcover) Price: € 57,19